Microbial metabolite drives ageing-related clonal haematopoiesis via ALPK1 - Puneet Agarwal; Avery Sampson; Kathleen Hueneman; Kwangmin Choi; Niels Asger Jakobsen; Emma Uible; Chiharu Ishikawa; Jennifer Yeung; Lyndsey Bolanos; Xueheng Zhao; Kenneth D. Setchell; David B. Haslam; et al. (Nature, 2025)
Abstract Clonal haematopoiesis of indeterminate potential (CHIP) involves the gradual expansion of mutant pre-leukaemic haematopoietic cells, which increases with age and confers a risk for multiple diseases, including leukaemia and immune-related conditions1. Although the absolute risk of leukaemic transformation in individuals with CHIP is very low, the strongest predictor of progression is the accumulation of mutant haematopoietic cells2. Despite the known associations between CHIP and increased all-cause mortality, our understanding of environmental and regulatory factors that underlie this process during ageing remains rudimentary. Here we show that intestinal alterations, which can occur with age, lead to systemic dissemination of a microbial metabolite that promotes pre-leukaemic cell expansion. Specifically, ADP-d-glycero-β-d-manno-heptose (ADP-heptose), a biosynthetic bi-product specific to Gram-negative bacteria3–5, is uniquely found in the circulation of older individuals and favours the expansion of pre-leukaemic cells. ADP-heptose is also associated with increased inflammation and cardiovascular risk in CHIP. Mechanistically, ADP-heptose binds to its receptor, ALPK1, triggering transcriptional reprogramming and NF-κB activation that endows pre-leukaemic cells with a competitive advantage due to excessive clonal proliferation. Collectively, we identify that the accumulation of ADP-heptose represents a direct link between ageing and expansion of rare pre-leukaemic cells, suggesting that the ADP-heptose–ALPK1 axis is a promising therapeutic target to prevent progression of CHIP to overt leukaemia and immune-related conditions.